If John solved the equation x? - 10x + 8 = 0 by completing the
square, one of the steps in his process would be
(1) (x-5)^2 = -8
(2) (x-5)^2 = 17
(3) (x+ 4)^2 = 10x
(4) (x + 4)^2 = 10x + 16

If John solved the equation x 10x 8 0 by completing the square one of the steps in his process would be 1 x52 8 2 x52 17 3 x 42 10x 4 x 42 10x 16 class=

Respuesta :

Answer:

[tex](x - 5)^{2} =17[/tex]

Step-by-step explanation:

[tex]x^{2} -10x = -8 \ add \ and \ subtract \ 25;\\x^2-10x+25-25= -8\\(x-5)^2 - 25 = -8\\(x-5)^2 = 17\\x-5=+\ \sqrt{17} \\\x_{1,} _{2} =5+\sqrt{17}[/tex]